FREQUENCY OF VALPROATE INDUCED THROMBOCYTOPENIA IN EPILEPTIC CHILDREN - Dr.Tahir Mehmood; Dr. Munazza Saleem; Syed Sajid Hussain Shah (Journal of University Medical & Dental College, 2014)
ABSTRACT: BACKGROUND: Valproic acid (VPA) is a commonly used antiepileptic drug in children as well as adult population. It is widely used as a first-line agent for patients with partial or generalized epilepsy. Thrombocytopenia is one of the common side effects associatedwith VPA therapy. OBJECTIVES: To find out the frequency of thrombocytopenia in epileptic children receiving valproate as monotherapy for more than 6 months, in POF Hospital, Wah Cantt. DESIGN: Descriptive cross-sectional study. PATIENTS AND METHODS: This study was a carried out at Neurology clinic of paediatric OPD of POF hospital Wah Cantt from January 2011 till June 2011. Eighty eight patients, 2-12 years of age with the diagnosis of epilepsy and taking valproate as monotherapy for more than 6 months in a dose of 30mg / kg or more were included in the study. The complete blood count was done and the diagnosis of thrombocytopenia was made with the platelet count less than 150 x 109/L. RESULTS: The frequency of thrombocytopenia in patients taking valproic acid as monotherapy was 19.3% and the children using higher doses of valproate were at higher risk of developing thrombocytopenia. CONCLUSION: About one fifth of the children taking valproate as monotherapy for more than 6 months in a dose of 30mg/kg or more had thrombocytopenia. The platelet count should be monitored for children receiving valproic acid especially on higher doses. Children using higher doses of valproate are at higher risk of developing thrombocytopenia.